Perceived Availability of Office Shared Spaces and Workplace Sitting: Moderation by Organizational Norms and Behavioral Autonomy - Sugiyama, T.; Hadgraft, N.; Healy, Genevieve; Owen, N.; Dunstan, D. (Sage Publications, 2018)
© 2018, The Author(s) 2018. A large amount of time spent sitting is a newly identified health risk. Although desk-based workers spend much of their time at work sitting, little is known about how office spaces may be related to workplace sitting time. This study examined cross-sectional associations of the perceived availability of office shared spaces with workers’ sitting time, and the potential role of workplace normative-social factors in the relationship. Participants (N = 221) wore an activity monitor (activPAL3) and reported availability of shared spaces (for formal meetings, informal discussion, collaborative working), organizational norms, and workplace behavioral autonomy. No shared-space variables were associated with workplace sitting time. However, the perceived availability of sufficient informal discussion space was associated with lower levels of sitting among those who reported more-supportive organizational norms and greater behavioral autonomy. These findings highlight environmental, organizational, and psychosocial factors that will be important to address in future initiatives to reduce work place sitting time.